2010
DOI: 10.1016/j.brainres.2010.08.088
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that obesity and androgens have independent and opposing effects on gonadotropin production from puberty to maturity

Abstract: Optimal fat mass is necessary for normal gonadotropin levels in adults, and both undernutrition and overnutrition suppress gonadotropins: thus, the gonadotropin response to relative adipose mass is biphasic. Adult obesity is associated with blunted luteinizing hormone (LH) pulse amplitude that is partially attributable to increased LH clearance rate. Testosterone appears to have a biphasic effect on gonadotropin production in females. Moderate elevations of testosterone appear to stimulate LH production at bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 106 publications
7
36
0
7
Order By: Relevance
“…Obese woman had significantly lower LH level responses to GnRH than the normal-weight group (17). Similar data also exist in obese girls without precocious puberty (2,6,7,18). Overweight early pubertal girls had significant blunting of sleeprelated LH production, which is the first hormonal change of puberty.…”
Section: Discussionsupporting
confidence: 63%
“…Obese woman had significantly lower LH level responses to GnRH than the normal-weight group (17). Similar data also exist in obese girls without precocious puberty (2,6,7,18). Overweight early pubertal girls had significant blunting of sleeprelated LH production, which is the first hormonal change of puberty.…”
Section: Discussionsupporting
confidence: 63%
“…Volume 76 | Number 6 | December 2014 interpretation could be via the suppressive effect of high adiposity on hypothalamic-pituitary gonal function (28) coupled with hyperandrogenemia (29), independent of its known paradoxic role of advancing puberty (28). Further research in children is needed to fully elucidate this complex interplay of hormones, nutrition and adiposity associated with physical growth and maturation and adverse health outcomes through young adulthood.…”
Section: Pre-and Postnatal Body Composition and Pubertal Hormonesmentioning
confidence: 99%
“…Moderately increased concentrations stimulate the synthesis of LH, while high concentrations have the opposite eff ect. Several studies have shown that women with abdominal obesity have higher levels of T and E2 compared to women with gluteofemoral obesity (Rosenfeld and Bordini, 2010).…”
Section: Introductionmentioning
confidence: 99%